Pengaruh Earning Per Share (EPS) Terhadap Harga Saham PT BNI Tbk - Tantianty, Caroline Wibawa; Uzliawati, Lia (Institut Bisnis dan Informatika Kesatuan, 2023)
Investment in the capital market is influenced by changes in the company's stock price, these changes are influenced by various factors, one of which is earnings per share (EPS). EPS is used as a ratio to assess the company's ability to pay dividends and a benchmark in assessing the company's performance. The higher the company's EPS level, the greater the profit generated by the company. This study aims to determine the effect of earnings per share on the stock price of PT BNI Tbk. This type of research is a quantitative research with a descriptive method, with a causal research design type. The data in this study used secondary data with data analysis methods consisting of descriptive statistical tests, classical assumption tests, simple regression analysis, coefficient of determination tests, and t tests. The test uses SPSS Ver 25 software. The results of the study explain that EPS has a significant positive effect on the stock price of PT BNI Tbk for the period 2012-2021 with a t-count value of 3.245 > 2.024 t-table value, significant level 0.002 <0.05.